A Clostridium difficile Lineage Endemic to Costa Rican Hospitals Is Multidrug Resistant by Acquisition of Chromosomal Mutations and Novel Mobile Genetic Elements - Ramírez Vargas, Gabriel (2017)
The antimicrobial resistance (AMR) rates and levels recorded for Clostridium difficile are on the rise. This study reports the nature, levels, diversity, and genomic context of the antimicrobial resistance of human C. difficile isolates of the NAPCR1/RT012/ST54 genotype, which caused an outbreak in 2009 and is endemic in Costa Rican hospitals. To this end, we determined the susceptibilities of 38 NAPCR1 isolates to 10 antibiotics from seven classes using Etests or macrodilution tests and examined 31NAPCR1 whole-genome sequences to identify single nucleotide polymorphisms (SNPs) and genes that could explain the resistance phenotypes observed. The NAPCR1 isolates were multidrug resistant (MDR) and commonly exhibited very high resistance levels. By sequencing their genomes, we showed that they possessed resistance-associated SNPs in gyrA and rpoB and carried eight to nine acquired antimicrobial resistance (AMR) genes. Most of these genes were located on known or novel mobile genetic elements shared by isolates recovered at different hospitals and at different time points. Metronidazole and vancomycin remain the first-line treatment options for these isolates. Overall, the NAPCR1 lineage showed an enhanced ability to acquire AMR genes through lateral gene transfer. On the basis of this finding, we recommend further vigilance and the adoption of improved control measures to limit the dissemination of this lineage and the emergence of more C. difficile MDR strains.